Garfield makes it big - Davis, Jim. (New York : Ballantine Books, 1985)
Contains reprints of the comic strip featuring America's funniest cat.
4.0
5-8
Keywords: Garfield (Fictitious character) -- Fiction; Cats -- Fiction; Cartoons and comics; Garfield (Fictitious character) -- Fiction; Cats -- Fiction; Comic books, strips, etc